The Effect of Alloy Compositions on The Microstructure and Mechanical Properties of Ceramic Matrix Composite Formed by Combustion Synthesis - Awallu, Yudha Rahman; Wijianto, W; Siswanto, Waluyo Adi (Prosiding Simposium Nasional Rekayasa Aplikasi Perancangan dan Industri, 2024)
In this research the purpose its to showing the effect of alloy compositions. This research was done by using powder form materials such as C, Al, and TiO2. By used formula 3TiO2 + (4+X) Al + 3C → 3TiC + 2Al2O3 + (X) Al, the powders reacted also with excess Al to see the different of effect that was done by combustion synthesis. The results from the research is to showing the efect of alloy by excess Al in the reactant composition, that excess Al from 20%, 40%, 60%, 80%, and 100%. The synthesis process will be done by using Arc Flame and argon, argon to minimize the oxidation from oxygen. The product from the research is Al2O3 aliminium alloys are alloys in which aluminium (Al) is the predominant metal. The typical alloying elements are copper, magnesium, silicon, tin, and zinc. About 85% of aluminium is used for wrought products, for example rolled plate, foils, and extrusion. To know what the effect from the excess of Al to the reactant, in this research the test will be done by using XRD test, SEM, and microhardness. XRD test used to know the phase of the product, in the other way SEM test used to show the composition of the product after burning process, and the last one microhardness test it’s done to know the physical properties.